Jonathan Edwards, The inner witness of the spirit, and experiential exegesis - Hoselton, Ryan P. (Jonathan Edwards studies, 2015)
This essay seeks to contribute to the growing literature on Jonathan Edwards’ exegesis and its importance to his thought and ministry. Many studies have examined Edwards’ epistemology and understanding of revelation in juxtaposition with Enlightenment thinkers like John Locke. While recognizing that Edwards’ post-Lockean intellectual context deeply impacted his thought, this essay demonstrates that Edwards also creatively drew from traditions of experimental piety in his exegesis. In his efforts to comprehend and bolster the emerging piety of the evangelical awakenings, Edwards exploited the Reformed doctrine of the Spirit’s inner testimony in order to invest individual religious experience with an elevated authority in biblical interpretation. This move not only impacted the emphases and substance of his exegesis—reflecting the concerns and themes of the early evangelical movement—but it also empowered individual lay believers with greater interpretive powers, consequently contributing to the populist character of early evangelical identity and the democratization of religious authority in America.